Combined Effect of Spent Mushroom Substrate and Agro-Industrial Residues on Pleurotus columbinus Production and Intra-Cellular Polysaccharide Synthesis - Marianna Dedousi; Chrysavgi Gardeli; Seraphim Papanikolaou; Panagiota Diamantopoulou (BioTech, 2025)
Spent mushroom substrate (SMS), spent coffee grounds from espresso production (SCG), faba bean harvest residues (FBR), pistachio shells (PS) wheat straw (WS) (control) agro-industrial waste were combined in different ratios, with or without supplements (wheat bran, soybean flour), to create novel substrates for Pleurotus columbinus growth. The impact of the substrates on the mycelial growth rate (Kr), biomass production, laccase, total cellulases and carbohydrate synthesis, along with the C and N consumption by P. columbinus, were examined in fully colonized substrates. The incubation period, earliness and biological efficiency (B.E.) (%) were also determined. Then, the intracellular polysaccharide (ICP) contents of the P. columbinus produced mushrooms were evaluated in the most promising substrates. P. columbinus was grown successfully in a wide range of C/N ratios of substrates and the fastest Kr (7.6 mm/d) was detected on the 70 SMS-30 FBR, without supplements, whereas substrates consisting of SCG enhanced biomass production (700.0–803.7 mg/g d.w.). SMS and PS or SCG led to the shortest incubation and earliness period of P. columbinus. The C content was reduced and the N content was substantially increased in all the colonized substrates. The 70 SMS-30 FBR and 80 SMS considerably enhanced the laccase production (up to 59,933.4 U/g d.w.) and substrates consisting of PS promoted total cellulases activities. Greater amounts of carbohydrates (3.8–17.4 mg/g d.w.) than that in the control were recorded for all the substrates. The combination of SMS and SCG or WS led to the highest B.E. values (59.3–87.1%) and ICP amounts (34.7–45.9%, w/w), regardless of the supplement addition. These findings support the effective utilization of agro-industrial waste in P. columbinus cultivation, producing high-value-added compounds and supporting mushroom growth.